The Influence of Think Talk Write (TTW) Learning Model on Critical Thinking Ability of Class VII Students of MTs Al-Ikhlas Mowewe - Nasruddin Nasruddin; Herlina Herlina; Ulfayanti Ulfayanti; Nisa Miftachurohmah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This experimental study aims to determine the effect of the application of the TTW learning model on the critical thinking skills of seventh grade students of MTs. Al Ikhlas Mowewe. The population in this study were all students of class VII MTs. Al Ikhlas Mowewe Academic Year 2020/2021. Sampling using a saturated sample technique. Learning outcomes data on students' mathematics were collected by using the test instrument given at the posttest. The results showed that the average value of critical thinking skills of student in class VIIA (31 students) and class VIIB (31 students) were 75 and 65. So, it’s indicates that the critical thinking ability of students who were taught using TTW learning was higher than using conventional learning. Furthermore, the results of inferential statistics analysis on hypothesis testing using the t-test have obtained the value of , indicating that   is rejected and  is accepted, it means, there is a significant difference of critical thinking skills of students by TTW learning and conventional learning. So, the conclusion of this study is that the critical thinking ability of students who are taught with TTW learning has a more positive effect than the critical thinking ability of students who are taught by conventional learning in class VII MTs. Al Ikhlas Mowewe.